Female production within the gall and male production on leaves by individual alates of a social aphid - S. Aoki (2018)
The social aphid Astegopteryx spinocephala forms a banana-bunch shaped gall, consisting of several subgalls, on Styrax benzoides in northern Thailand. The aphid's life cycle is non-host alternating. Alates (sexuparae) containing both male and female embryos appear near the end of the dry season, when many sexuals and eggs are found in subgalls guarded by sterile soldiers. Our experiments revealed that these alates give birth to almost all (99%) females within the natal subgall before flying but most (73-86%) males on leaves of the host tree after flying, and that these first-instar males intrude into live subgalls for mating. The fact that some (14-27%) males are deposited in the natal subgall indicates the occurrence of both outbreeding and inbreeding, or some level of local mate competition (LMC), in this mating system. However, the primary (investment) sex ratio was estimated to be near 0.5. This suggests that factors other than LMC, a candidate for which is local resource competition, might also affect the sex ratio in A. spinocephala. © 2007 Birkhaeuser.